The Politics and Science of Prevision : Governing and Probing the Future. - Wenger, Andreas. (CSS Studies in Security and International Relations Series, 2020)
This book inquires into the use of prediction at the intersection of politics and academia, and reflects upon the implications of future-oriented policymaking across different fields.